Poland-Turkey comparison of mobile payments quality in pandemic time - Witold Chmielarz; Marek Zborowski; Alicja Fandrejewska; Mesut Atasever (Journal of Risk and Financial Management, 2021)
The main objective of this article is to identify and analyze the use of mobile payments in two countries, Poland and Turkey. The data for the study were collected with the application of the CAWI method in March 2021. The survey covered nearly 650 respondents in total. The basis for comparisons was populations from two culturally distinct countries, Poland and Turkey, which are at a similar level of development as regards the use of the Internet. The studies were carried out simultaneously in both countries and examined the group of young people aged 18-25. The research surveyed the population, which included the most active Internet users who are taking full advantage of the benefits of globalization, which is facilitated by the development of the Internet worldwide. The survey was translated into the respondents' native languages, initially validated during the pilot studies and then distributed and circulated among the study participants. The obtained findings were subject to comparison, and the differences between the samples were analyzed and commented on to verify the hypotheses formulated in the study. The main limitation of the conducted study was the selection of a random group-the research sample consisted only of members of the academic community. The study presented in the article fills the research gap regarding international comparisons of the use of m-payments in the period of the COVID-19 pandemic. The obtained results indicate the undoubted fact of increased interest in the use of m-payments in e-commerce and e-banking, and even more importantly, differences concerning 40% of the criteria/attributes applied to assess the use of m-payments in both countries. The findings can be used by business practitioners dealing with the development of m-payments. Another potential application is to attempt to bridge the gaps between countries, which may be supported by globalization processes.
Keywords: 330; e-banking; international comparison; m-banking; m-payments; pandemic COVID-19